2022
DOI: 10.3390/ma15062207
|View full text |Cite
|
Sign up to set email alerts
|

pH and Redox Dual-Responsive Mesoporous Silica Nanoparticle as Nanovehicle for Improving Fungicidal Efficiency

Abstract: Prochloraz (Pro) controlled-release nanoparticles (NPs) based on bimodal mesoporous silica (BMMs) with redox and pH dual responses were successfully prepared in this study. BMMs was modified by a silane coupling agent containing a disulfide bond, and β-cyclodextrin (β-CD) was grafted on the surface of the NPs through host–guest interaction. Pro was encapsulated into the pores of nanoparticles by physical adsorption. NPs had a spherical structure, and their average diameter was 546.4 ± 3.0 nm as measured by dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Wu et al prepared mesoporous silica controlled-release nanoparticles (546.4 nm) with dual redox and pH response, and the results showed that excellent pH/redox dual response release performance was achieved under acidic conditions, which is consistent with our study. 36 The earlier results indicate that DMM@HMS-SS-COS exhibited good controlledrelease properties, which is beneficial for long-term disease control in leaves.…”
Section: Controlled-release Kineticsmentioning
confidence: 94%
“…Wu et al prepared mesoporous silica controlled-release nanoparticles (546.4 nm) with dual redox and pH response, and the results showed that excellent pH/redox dual response release performance was achieved under acidic conditions, which is consistent with our study. 36 The earlier results indicate that DMM@HMS-SS-COS exhibited good controlledrelease properties, which is beneficial for long-term disease control in leaves.…”
Section: Controlled-release Kineticsmentioning
confidence: 94%
“…To achieve acidic pH influenced release of pesticide from PSNs, surface functionalization of PSNs by low-pH-sensitive linkers have been used in several studies. ,,, For instance, Liang and co-workers developed a pH-responsive pesticide delivery system using coordination of Cu ions and tannic acid on MSN loaded with pyraclostrobin (Pyr) (MSNs-TA-Cu@Pyr). They evaluated the release profile of Pyr at different pH values (4.5, 6.0, and 7.4) at ambient temperatures.…”
Section: Porous Silica Nanomaterials (Psns) For Pesticide Deliverymentioning
confidence: 99%
“…In summary, the ability to release the pesticide dimethomorph (DMM) was improved by cleaving the disulfide bond in the presence of glutathione, making the HSN modified with a disulfide bond and capped with chitosan oligosaccharide (COS)@DMM a highly effective redox-responsive pesticide formulation. PSNs also successfully delivered avermectin and prochloraz using a similar strategy.…”
Section: Porous Silica Nanomaterials (Psns) For Pesticide Deliverymentioning
confidence: 99%
“…[127][128][129][130] For instance, Wu et al prepared prochloraz (Pro) controlled-release nanoparticles against fungi based on bimodal mesoporous silica (BMM) with redox and pH dual responses. 131 (Fig. 11) In addition, Huang et al developed a controlled drug release system using near-infrared light (NIR) and external stimulation of protein coating.…”
Section: Inorganic-based Npsmentioning
confidence: 99%
“…Fig.11(A) Schematic diagram of pH and redox dual-responsive mesoporous silica nanoparticle 131. (B) Schematic diagram of lysozyme and near-infrared light-responsive drug delivery system 132.…”
mentioning
confidence: 99%